Genomic Insights of Enterococcus faecium UC7251, a Multi-Drug Resistant Strain From Ready-to-Eat Food, Highlight the Risk of Antimicrobial Resistance in the Food Chain - Belloso Daza, Mireya Viviana; Milani, Giovanni; Cortimiglia, Claudia; Pietta, Ester; Bassi, Daniela; Cocconcelli, Pier Sandro (Frontiers in Microbiology, 2022)
The presence of multi-drug resistant (MDR) bacteria in ready-to-eat foods comprises a threat for the public health due to their ability to acquire and transfer antibiotic-resistant determinants that could settle in the microbiome of the human digestive tract. In this study, Enterococcus faecium UC7251 isolated from a fermented dry sausage was characterized phenotypically and genotypically to hold resistance to multiple antibiotics including aminoglycosides, macrolides, β-lactams and tetracyclines. We furtherly investigated this strain following a hybrid sequencing and assembly approach (short and long reads) and determined the presence of various mobile genetic elements (MGE) responsible for horizontal gene transfer (HGT). On the chromosome of UC7251, we found one Integrative Conjugative Element (ICE) and a conjugative transposon Tn916 carrying tetracycline resistance. UC7251 carries two plasmids, one small plasmid harboring a rolling circle replication and one MDR megaplasmid. The latter was identified as mobilizable and containing a putative integrative conjugative element-like region, prophage sequences, insertion sequences, heavy-metal resistance genes and several antimicrobial resistance (AMR) genes confirming the phenotypic resistance characteristics. The transmissibility potential of AMR markers was observed through mating experiments where Tn916-carried tetracycline resistance was transferred at intra- and inter-species level. This work highlights the significance of constant monitoring of products of animal origin, especially RTE foodstuffs, to stimulate the development of novel strategies in the race for constraining the spread of antibiotic resistance.